2000
DOI: 10.12968/jowc.2000.9.1.25939
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced skin lesions in pigs: reperfusion injury and the effects of vitamin E

Abstract: The pathogenesis of the development of pressure ulcers is still unclear. The aim of this study was to investigate the role of ischaemia and reperfusion in pressure-induced tissue necrosis in the trochanteric region in pigs. Pressure application was achieved with a newly developed computer-controlled pressure device. Histological examination showed damage in the subcutis and muscle tissue comparable with inflammation, extending in a vascular pattern beyond the area of pressure application. Electron-microscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 5 publications
3
52
0
3
Order By: Relevance
“…However, at higher pressures (35kPa and 70kPa), extensive damage was reported immediately after the first day of loading. On the other hand, 50kPa pressure on pig trochanter for 2 hrs did not result in noticeable histopathological signs immediately upon cessation of loading (134). Histological signs of damage in subcutaneous tissues and muscles started to appear 1 hr after pressure cessation.…”
Section: Reperfusion and Flowmotionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, at higher pressures (35kPa and 70kPa), extensive damage was reported immediately after the first day of loading. On the other hand, 50kPa pressure on pig trochanter for 2 hrs did not result in noticeable histopathological signs immediately upon cessation of loading (134). Histological signs of damage in subcutaneous tissues and muscles started to appear 1 hr after pressure cessation.…”
Section: Reperfusion and Flowmotionmentioning
confidence: 83%
“…In animal studies, ischemia reperfusion injury has been demonstrated in the context of pressure ulcers (92,(134)(135)(136)). An adaptive effect of skin perfusion was reported in healthy subjects, where tissue oxygenation remained unaffected after a number of loading cycles.…”
Section: Reperfusion and Flowmotionmentioning
confidence: 99%
“…Previous studies showed that hypoxic injury of skin was intimately associated with oxidative stress and inflammatory responses (Houwing et al, 2000;Peirce et al, 2001). Mounting evidence suggested that cyclooxygenase-2 (COX-2) and its product prostaglandin E 2 (PGE 2 ) played a pivotal role in inflammatory response (Birnbaum et al, 2005;Chi and Kim, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other theories for the onset of tissue damage include collapse of capillaries and lymph nodes [29][30][31], reperfusion injury [32][33][34], and cell deformation under pressure [5,33,35]. The last has been studied using finite element (FE) models with a damage threshold law derived from previous experiments [4,36].…”
Section: Introductionmentioning
confidence: 99%